2017
DOI: 10.4081/monaldi.2017.791
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based cardiac rehabilitation in cardiac resynchronization therapy recipients: A primer for practicing clinicians

Abstract: Cardiac resynchronization therapy (CRT) is a therapeutic option of increasing importance for chronic heart failure (CHF) and criteria for implantation now concern a large amount of patient populations. As a consequence, subjects with ongoing CRT (or immediately after CRT implantation) are more often referred to Cardiac Rehabilitation (CR) programmes, and it has been recently estimated that about one third of CHF patients attending CR in Italy currently have this kind of device. The presence of CRT represents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…The possible explanation for these results is that the significant favorable effect of exercise training on events in those without a device was abrogated by the presence of BiV pacing (Zeitler et al, 2015). The most appropriate time window is not clear; it has also been recommended that exercise training begins at least 1 week after CRT implantation (Ambrosetti et al, 2017). The interval time between CRT implantation and exercise training in the included studies reported was at least 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation for these results is that the significant favorable effect of exercise training on events in those without a device was abrogated by the presence of BiV pacing (Zeitler et al, 2015). The most appropriate time window is not clear; it has also been recommended that exercise training begins at least 1 week after CRT implantation (Ambrosetti et al, 2017). The interval time between CRT implantation and exercise training in the included studies reported was at least 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This includes skin healing, which then should be responded by restriction of upper extremity motions. 22 However, after 24 hours of device implantation, light upper extremity motion will be required to obtain a positive effect on joint immobilization. 24 It was shown through a meta-analysis of exercises in patients with CRT and CRT-D that there is a 5% chance of device malfunction during the first 12 months after implantation, and 1.8% chance of infection at the implantation site, which then highlights the need of wound monitoring.…”
Section: Initial a Ss E Ss Mentmentioning
confidence: 99%
“…[18][19][20][21] In the context of exercise in CRT-D recipients, it is essential to determine shock threshold as it was mentioned that ICD shocks are associated with reduced quality of life, hence, would affect exercise compliance and physical activity. 10,22,23 Recent Cochrane meta-analysis had shown that studies on exercise in ICD recipients have better effects toward receiving appropriate shocks, however, this result was still inconclusive because of low level of available evidence. 10,11 Studies had mentioned that resting parasympathetic tone was found to raise along with exercise, and this would further protect against ventricular arrhythmias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A reszinkronizációs kezelésben részesültek többsége részesül a rehabilitációs edzésprogramokban, Olaszországban a résztvevők mintegy harmadát ők teszik ki [29].…”
Section: Rehabilitáció Különböző Cardialis Betegségekbenunclassified